Differential evolution based small signal modeling of GaN HEMT. Issue 6 (17th January 2019) - Majumdar, Arijit; Chatterjee, Soumyo; Bose, Sulagna; Chatterjee, Sayan; Chaudhari, Sheli S.; Poddar, Dipak R.
Abstract: In this article differential evolution based method of small signal modeling of GAN HEMT has been investigated. The method uses a unique search space exploration strategy to obtain optimized values of intrinsic and extrinsic elements pertaining to compact small signal model from extracted equivalent circuit elements and measured S‐parameter data. Effectiveness of the method has been illustrated by comparing the measured S‐parameter data of a 4 × 0.1 × 75 μm 2 GaN/SiC HEMT in the frequency range of 1 to 30 GHz wherein modeled and measured data are in good agreement.